The Effect of Rehabilitative Exercises on the Efficiency of the Knee Joint for Female Students with Simple Rupture of the Lateral Collateral Ligament - Rehab Nabeel Abd Alazem; Ammar Hamza Hadi; Mayson Hussien Alwan (Institute of Medico-legal Publications Pvt Ltd, 2021)
The research problem lies in the presence of large numbers of female students with knee joint, especiallyin the effectiveness of rhythmic gymnastics because this event requires a high level of skillful performancebecause most of the skills need to move quickly, jump and change direction, and that the lack of strength inthe muscles surrounding the knee joint exposes students to a lateral collateral ligament injury, and becausethese muscles are among the most important muscles that participate in motor performance and which beara high rate of effort performed and this may lead to the occurrence of injury, and that the use of treatmentwith chemical analgesic drugs over long periods of time usually causes many side effects, so the researchersdecided to use rehabilitating exercises that are of great benefit to such an injury to him, so rehabilitativeexercises were used in the rehabilitation of the lateral collateral ligament injury of the knee joint, the researchobjectives to prepare rehabilitative exercises in the efficiency of the knee joint for female students with asimple tear of the lateral ligament. The researchers used the experimental method in the method of (onegroup) with the two pre and post-tests due to its suitability to the nature of the problem. The sample waschosen by the intentional method of (7) students with partial tearing of the lateral ligament of the knee jointbased on a medical report from the specialist doctor, and after a medical examination and an (MRI). In lightof the results reached by the researchers, the following conclusions came out:- The rehabilitative exerciseshave a positive effect in rehabilitating the partial tear of the lateral ligament for students with rhythmicgymnastics.